The kynurenine pathway is activated in human obesity and shifted toward kynurenine monooxygenase activation. (8th September 2015) - Favennec, Marie; Hennart, Benjamin; Caiazzo, Robert; Leloire, Audrey; Yengo, Loïc; Verbanck, Marie; Arredouani, Abdelilah; Marre, Michel; Pigeyre, Marie; Bessede, Alban; Guillemin, Gilles J.; Chinetti, Giulia; et al.
<x xml:space="preserve">Abstract</x> Objective This study characterized the kynurenine pathway (KP) in human obesity by evaluating circulating levels of kynurenines and the expression of KP enzymes in adipose tissue. Methods Tryptophan and KP metabolite levels were measured in serum of individuals from the D.E.S.I.R. cohort (case–cohort study: 212 diabetic, 836 randomly sampled) and in women with obesity, diabetic or normoglycemic, from the ABOS cohort (n = 100). KP enzyme gene expressions were analyzed in omental and subcutaneous adipose tissue of women from the ABOS cohort, in human primary adipocytes and in monocyte‐derived macrophages. Results In the D.E.S.I.R. cohort, kynurenine levels were positively associated with body mass index (BMI) (P = 4.68 × 10−19) and with a higher HOMA2‐IR insulin resistance index (P = 6.23 × 10−4). The levels of kynurenine, kynurenic acid, and quinolinic acid were associated with higher BMI (P < 0.05). The expression of several KP enzyme genes (indoleamine 2, 3‐dioxygenase 1 [IDO1], kynureninase [KYNU], kynurenine 3‐monooxygenase [KMO], and kynurenine aminotransferase III [CCBL2]) was increased in the omental adipose tissue of women with obesity compared to lean (P < 0.05), and their expression was induced by proinflammatory cytokines in human primary adipocytes (P < 0.05), except for KMO that is not expressed in these cells. The expressions of IDO1, KYNU, KMO, and CCBL2 were higher in proinflammatory than in anti‐inflammatory macrophages (P < 0.05). Conclusions In the context of obesity, the presence of macrophages in adipose tissue may contribute to diverting KP toward KMO activation.